Legitimacy of a child through acknowledgement (Al-Iqrar) under Islamic Law: the extent to which acknowledgement establishes paternity of an illegitimate child - Mohd., Azizah (IIUM Press, 2009)
Illegitimacy is not a new issue. However, cases on illegitimacy in Malaysia have brought attention the stigma which is hardly ever removed. The term illegitimate child seems to downgrade a child's status. Islamic law provides several methods of legitimation, which if not clearly understood will invite controversy. Thus, this article seeks to examine the methods of legitimizing an illegitimate child particularly by acknowledging the extent it establishes paternity of the child. This is especially so when it has already proven that the child is illegitimate. Other methods to establish paternity of a child are also briefly discussed in order to provide the ground rules for the overall concept. The examination of the provision of Islamic law in Malaysia particularly the Islamic Family Law (Federal Territories)Act 1984 will also be discussed extensively.